The Vital Role of Cloud Healthcare During COVID-19 Pandemic - Amen Adnan (Newinera Publisher, 2022)
The most sharable tag on social media was “stay at home”. Where, the governments oblige their residents from physical meeting or traveling instead of this they have to stay at their home for controlling the wide speared of The novel Corina Virus (COIVD-19). Hence, many lives are being saved. Here, Cloud Computing act as a game changer in many institutions and countries demand particularly to healthcare organizations. This Paper will review cloud health applications such as Telehealth, Telemedicine supporting with mobile cloud health applications. And the important role of sharable the cloud informatics in health. Then it focuses on the role of cloud played in health care sector to saving life’s during COIVED -19. Not only for people who have been infected but also for assisting other older people to get their treatment. Some concerns are existing to discuss related with security, outages, privacy and monitoring issues or when matter went wrong during the Telemedicine appointment with suggested solution for future matters.